The necessity of pen replication to account for and understand the impacts of social dynamics on individual laying hen behavior - Campbell, Dana L. M.; Horton, Brian J. (Frontiers in Animal Science, 2023)
Individual laying hens within the same group show variation in their temperament traits and cognitive learning abilities which can be affected by both their early rearing experiences and housing environments. Hens also have distinct individual patterns of movement within housing systems which may correlate with temperament and cognition. Individual behavioural tests can measure treatment impacts, but social dynamics may impact on an individual's behaviour. The aims of this perspective piece are to provide further evidence of pen level variation using original data on social ranging patterns and fear assessment of free-range hens exposed to different enriched rearing environments; and to encourage more studies to consider pen replicate variation to better understand causes and mechanisms. A literature review showed while most published studies over the past decade assessing individual laying hen behaviour included group level replication (83% of 54 articles reviewed), almost none considered inter-pen variation. Original data analysis of individual hens' range use recordings showed significant treatment pen replicate variation in pop-hole following movements and hen-pair associations in time spent together inside or outside. Significant inter-pen variation was also seen in tonic immobility tests on a subset of hens from the same study. Pen-level replication is important for scientific validity and for improving our understanding of why commercial flocks in the same environment can be so variable in their behaviour to inform management practices. Further research could help to understand the mechanisms behind why groups reared and housed in the same environments will show significant inter-group variation.